Proceso de innovación y desarrollo de productos en las MYPES - Lozano Rocha, Claudia Patricia (2025)
The purpose of this research was to determine the influence of the innovation process on product development in MSEs, Opting for a basic study, descriptive correlational level and non-experimental cross-sectional design, the sample consisted of 100 entrepreneurs for the survey conducted with a questionnaire for data collection. The findings show that the innovation process is high (65%); product development is also rated as high (65%); therefore, it is determined that the variables have a significance of p=0.000. Likewise, the dimension level, driver, direction, origin and locus have a significance of p=0.000, these dimensions have a positive and significant influence on product development.